Penerapan Model Pembelajaran Kooperatif Tipe LT (Learning Together) Terhadap Hasil Belajar Passing Atas dalam Permainan Bola Voli Siswa Kelas VIII-C SMP Negeri 3 Rancaekek Tahun Pelajaran 2016-2017 - Farida, Ida (STKIP Andi Matappa Pangkep, 2021)
The purpose of this research is to describe how to use the learning together model to improve students' understanding of passing in the volleyball game Class VIII-C at SMP Negeri 3 Rancaekek in the 2016/2017 academic year. In addition, this study specifically aims to describe the procedure for using the learning together model which can improve students' understanding of passing in volleyball games for Class VIII-C of SMP Negeri 3 Rancaekek in the 2016/2017 academic year. The research design used is classroom action research from Kurt Lewin in Trianto (2010:29). As for each action effort to achieve these goals are designed in one unit as a cycle. Each cycle consists of 4 stages, namely: planning (planning), action (acting), observation (observing), and reflection (reflecting). Data collection techniques and instruments This research uses several techniques, including the technique used by researchers in collecting data is test, observation sheets and documentation of learning activities. Based on the research results that have been described and confirmed by theoretical studies, it can be concluded that the use of the Learning Together type of cooperative learning model in learning volleyball games with overhead passing material can improve learning outcomes and activities of Class VIII-C students at SMP Negeri 3 Rancaekek.